Perspectives of teachers of students with intellectual disabilities on the role of educational policies and systems in using Universal Design for Learning: A qualitative study - Sarah Khaled Alfawzan (PLoS ONE, 2025)
Universal Design for Learning is among the inclusive frameworks that has been incorporated in policies such as the “Every Student Succeeds Act of 2015” and the “Higher Education Opportunity Act of 2008”. However, little is known about the factors that influence its use with students with intellectual disabilities, while their teachers play a critical role in understanding those factors. Currently, there is a paucity of research that has examined their perspectives in Saudi Arabia. Thus, the objective of this qualitative study was to explore teachers’ perspectives on the role of educational policies and systems in using universal design for learning with their students. 14 teachers of students with intellectual disabilities were interviewed during the study. In the findings, the participants identified a number of factors that hinder its use, including: educational supervision; school management practices, and lack of access to the general curriculum, in addition to solutions to address them, such as providing legal/legislative support and funding for programs. The findings revealed unique experiences as well as commonalities among teachers, which are particularly important for policymakers, supervisors, principals, and teachers. Implications for future research, policy, and practice were presented.